FORENSIC STRUCTURAL ASSESSMENT OF MAHAKAM BRIDGE AFTER BARGE COLLISION: DAMAGE EVALUATION AND ANALYSIS - Tukimun, Tukimun; Aco Wahyudi Efendi; Andi Muhammad Ade Satriya (LPSDI Bina Patria, 2025)
In an attempt to maintain safety and functionality, bridge structures—which are essential parts of transportation infrastructure—must be resilient to unintentional events like vessel collisions. After colliding with the IS-28 ship on February 16, 2025, the Mahakam Bridge in Samarinda, Indonesia, suffered significant structural damage, especially at Pier 3. In order to evaluate the extent of the damage and the structural integrity, this study presents a forensic examination of the occurrence that combined visual inspection, dimensional measurements, and Finite Element Method (FEM) analysis. Important discoveries included spalling and exposed reinforcement bars, as well as considerable cracking in the downstream pile top with thicknesses of up to 1.3 mm and lengths of up to 4.57 meters. Furthermore, expansion joint misalignments were found, as evidenced by the left span's gradual elongation over seven years, from 4.3 cm to 5.2 cm. Critical stress concentrations were found via FEM calculations, with compressive stresses exceeding the material limit of 9,000 kN/m² and tensile stresses reaching 75 MPa. Furthermore, differences between 3D scanning and video-based evaluations brought to light the importance of precise measuring methods in structural analysis. To increase the bridge's resistance against future crashes, the study emphasizes the necessity of impact-resistant designs, targeted retrofitting techniques, and ongoing structural monitoring. This study fills a significant knowledge gap in regional forensic engineering and offers useful information for risk reduction and bridge restoration in maritime settings.